Reanalysis of 2 metritis studies demonstrates different patterns of postpartum uterine infection for primiparous versus multiparous cows - J.C.C. Silva; M.C. Lucy (JDS Communications)
Metritis typically has a greater incidence in primiparous compared with multiparous cows. In separate studies with similar design, we noted that primiparous and multiparous cows responded differently to a model developed to induce metritis via the intrauterine infusion of a bacterial challenge of Fusobacterium necrophorum, Trueperella pyogenes, and Escherichia coli. To understand the difference between primiparous and multiparous cows, we reanalyzed the relative abundance of bacteria genera within the vaginal microbiome during the first 2 wk postpartum from the 2 previous studies for primiparous and multiparous cows. We conducted a first reanalysis of primiparous and multiparous cows that received an identical challenge dose (106 cfu of each pathogen) and a second reanalysis that compared all primiparous and multiparous cows that were or were not diagnosed with metritis regardless of challenge dose (0, 103, 106, or 109 cfu per pathogen). The challenge model resulted in clinical metritis in both primiparous and multiparous cows, although some control cows (0 dose) developed metritis and, conversely, some bacterial challenge cows failed to develop metritis. Importantly, cows that contracted metritis had increased and sustained relative abundance of key metritis pathogens including Fusobacterium, Porphyromonas, Helcococcus, and Trueperella after calving regardless of parity. We unexpectedly found, however, that primiparous cows that did not develop metritis had a different bacterial profile (based on 16S ribosomal gene sequencing as well as bacterial culture) compared with multiparous cows that did not develop metritis. In primiparous nonmetritis cows, the relative abundance of the genera Fusobacterium, Porphyromonas, Helcococcus, and Trueperella was almost identical to primiparous metritis cows during the first week postpartum, but the relative abundances in nonmetritis cows decreased rapidly thereafter. The relative abundance of the same genera in nonmetritis multiparous cows did not increase or increased to a lesser extent postpartum. The different patterns of infection for nonmetritis primiparous (initial increase in relative abundance [wk 1] followed by a decrease [wk 2]) compared with nonmetritis multiparous cows (stable and low-level relative abundance for 2 wk postpartum) was found when the analysis included only challenge cows (106 cfu dose) or all cows regardless of dose. We found different patterns of infection for primiparous compared with multiparous cows. This observation may explain lesser incidence of metritis in multiparous compared with primiparous cows.